The Dynamic Relationship between the Foreign Exchange Exposure and Stock Markets: Evidence during the Global Economic Crisis - Ab RAHMAN, Nik Muhamad Naziman; NAZIMAN, Yusrina hayati Nik Muhd; RAHMAN, Amri Ab (Asian Journal of Empirical Research, 2013)
This paper examines the dynamic linkages between the foreign exchange and stock markets for five East Asian countries, including Hong Kong, Japan, Malaysia, Singapore, and Thailand. While the literature suggests the existence of significant Interactions between the two markets, our empirical results show that, in general, exchange rates Granger-cause stock prices with less significant causal relations from stock prices to exchange rates. Furthermore, this one-way Granger causality effect from exchange rates to stock prices becomes less significant during the US financial crisis of 2009. Our results also suggest that, there is insignificant long-run outlook (no cointegration) except for Hong Kong, implies that these financial assets share on common trends in their economy system and hence they will move apart in the long-run for countries that have higher trade size exchange rate fluctuations tend to exhibit significant influence on the equity market, regardless of the exchange rate arrangement system and the degree of capital controls during the US financial crisis of 2009.